Esculetin Provides Neuroprotection against Mutant Huntingtin-Induced Toxicity in Huntington's Disease Models - Letizia Pruccoli; Carlo Breda; Gabriella Teti; Mirella Falconi; Flaviano Giorgini; Andrea Tarozzi (MDPI AG, 2021)
Huntington's disease (HD) is a neurodegenerative disorder caused by an abnormal CAG trinucleotide repeat expansion within exon 1 of the huntingtin (HTT) gene. This mutation leads to the production of mutant HTT (mHTT) protein which triggers neuronal death through several mechanisms. Here, we investigated the neuroprotective effects of esculetin (ESC), a bioactive phenolic compound, in an inducible PC12 model and a transgenic Drosophila melanogaster model of HD, both of which express mHTT fragments. ESC partially inhibited the progression of mHTT aggregation and reduced neuronal death through its ability to counteract the oxidative stress and mitochondria impairment elicited by mHTT in the PC12 model. The ability of ESC to counteract neuronal death was also confirmed in the transgenic Drosophila model. Although ESC did not modify the lifespan of the transgenic Drosophila, it still seemed to have a positive impact on the HD phenotype of this model. Based on our findings, ESC may be further studied as a potential neuroprotective agent in a rodent transgenic model of HD.